Wafer‐Scale Organic Complementary Inverters Fabricated with Self‐Assembled Monolayer Field‐Effect Transistors. (6th August 2020) - Zhao, Baolin; Gothe, Bastian; Sarcletti, Marco; Zhao, Yuhan; Rejek, Tobias; Liu, Xin; Park, Hyoungwon; Strohriegl, Peter; Halik, Marcus
Abstract: Self‐assembled monolayers (SAMs) of π‐conjugated molecules can achieve robust charge transport by the formation of ordered 2D layers at the desired regions, which enable their application for organic integrated circuits. Here, the self‐assembled monolayer field‐effect transistor concept is applied as a scalable method to realize fully integrated complementary inverters by stepwise semiconductor deposition. Two‐component stacked bilayer ambipolar transistors are fabricated by semiconducting self‐assembled monolayers (n‐SAM or p‐SAM) as the bottom layer and a complementary thin‐film semiconductor layer on top. The integrated complementary metal‐oxide‐semiconductor like (CMOS‐like) inverter achieves proper logic performances. The nanometer‐thin monolayers exhibit effective charge transport and their flat, homogeneous surfaces benefit the interconnected growth of the top layer. Furthermore, by controlling the solution‐based and region‐selective deposition of p‐ and n‐type SAMs, fully integrated CMOS inverters are realized on wafer scale by photolithography for the first time. The CMOS inverters show a nearly 100% yield with a gain up to 48, and noise margin 3.68 V (73.6% of VDD /2). The strategy of semiconducting SAMs for digital logic gates demonstrates a reliable approach for sophisticated large‐area circuits. Abstract : Here, a new method to fabricate fully integrated organic complementary inverters based on self‐assembled monolayer field‐effect transistors on a large area is realized. Complementary metal‐oxide‐semiconductor‐like (CMOS‐like) and CMOS inverters are fabricated by stepwise semiconductor deposition via photolithography. These devices exhibit high yield and reproducibility with a gain up to 48 and a noise margin of 73.6% of V DD /2.